Measurement of Refractive Index Ranging from 1.42847 to 2.48272 at 1064 nm Using a Quasi-Common-Path Laser Feedback System*Supported by the National Natural Science Foundation of China under Grant No 61036016, and the Beijing Higher Education Young Elite Teacher Project under Grant No YETP0086. (September 2015) - Xu, Ling; Tan, Yi-Dong; Zhang, Shu-Lian; Sun, Li-Qun
<x content-type="archive" xml:space="preserve">Abstract</x> Wavelength 1064 nm is one of the most widely used laser wavelengths in industries and science. The high-precision measurement of the refractive index of optical materials at 1064 nm is significant for improving the optical design. We study the direct measurement of refractive index at 1064 nm of lasers, including calcium fluoride (CaF2), fused silica and zinc selenide (ZnSe), whose refractive indices cover a large range from 1.42847 to 2.48272. The measurement system is built based on the quasi-common-path Nd:YAG laser feedback interferometry. The thickness can be measured simultaneously with the refractive index. The results demonstrate that the system has absolute uncertainties of ∼10−5 and ∼10−4 mm in refractive index and thickness measurement, respectively.